2021
DOI: 10.3390/s21051921
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Driven Noise Reduction for Reduced Flux Computed Tomography

Abstract: Deep neural networks have received considerable attention in clinical imaging, particularly with respect to the reduction of radiation risk. Lowering the radiation dose by reducing the photon flux inevitably results in the degradation of the scanned image quality. Thus, researchers have sought to exploit deep convolutional neural networks (DCNNs) to map low-quality, low-dose images to higher-dose, higher-quality images, thereby minimizing the associated radiation hazard. Conversely, computed tomography (CT) me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…14 Deep learning (DL) has been explored in recent years for CT noise-reduction as part of the image reconstruction or the post-processing. [14][15][16][17][18][19][20][21] When proper training datasets are used, DL has shown significant noise-reduction capability while preserving the FBP-like peak-frequency in NPS. In DL, the production of the ground-truth images (GTI) is critical, since DL relies heavily on large training datasets to achieve high accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…14 Deep learning (DL) has been explored in recent years for CT noise-reduction as part of the image reconstruction or the post-processing. [14][15][16][17][18][19][20][21] When proper training datasets are used, DL has shown significant noise-reduction capability while preserving the FBP-like peak-frequency in NPS. In DL, the production of the ground-truth images (GTI) is critical, since DL relies heavily on large training datasets to achieve high accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Deep learning (DL) has been explored in recent years for CT noise‐reduction as part of image reconstruction or post‐processing 19–28 . To further enhance the noise‐reduction capability, a dynamically selected image volume is utilized to produce a single image 29 .…”
Section: Introductionmentioning
confidence: 99%
“…The authors compared the effect of different loss functions and found that the least absolute deviation (L1) loss gave a better result in terms of peak signal to noise ratio (PSNR) and structural similarity index measure (SSIM) when compared to the least square errors (L2) loss, SSIM loss, and Visual Geometry Group (VGG) perceptual loss. Recently, Alsamadony et al (2021) acquired low-exposure and high-exposure CT scans on the same carbonate sample and compared denoising performance using a pre-trained very deep super resolution (VDSR) network against a shallow U-Net. They demonstrated that DL-based image processing can improve image quality; and that pre-trained VDSR network with fine-tuning tends to out-perform VDSR trained from scratch.…”
Section: Background and Introductionmentioning
confidence: 99%